Global existence of bounded solutions to the relativistic BGK model. (February 2022) - Hwang, Byung-Hoon
Abstract: The relativistic BGK model is a representative relaxation-time approximation of the relativistic Boltzmann equation. In this paper, we prove the global existence of bounded solutions to the relativistic BGK model proposed by Anderson and Witting when the initial data satisfies the excess conservations of mass and energy, and the excess entropy inequality from global equilibrium. The L ∞ estimate established in Guo (2010) is the main ingredient of the proof.